Celastrol improves the therapeutic efficacy of EGFR-TKIs for non-small-cell lung cancer by overcoming EGFR T790M drug resistance. Issue 8 (September 2018) - Wang, Ying; Liu, Qiuyun; Chen, Haojie; You, Jun; Peng, Bin; Cao, Fanfan; Zhang, Xue; Chen, Qing; Uzan, Georges; Xu, Limin; Zhang, Denghai
Abstract : The development of resistance to therapy continues to be a serious clinical problem in lung cancer management. Epidermal growth factor receptor tyrosine kinase inhibitor (EGFR-TKI) is one of the most common chemotherapy drugs to treat non-small-cell lung cancer. However, almost all treatments fail after ∼1 year of treatment because of drug tolerance, probably occurring from the threonine 790 mutation (T790M) of the EGFR, resulting in overactivation of the EGFR. Celastrol is a natural compound that exhibits antiproliferative activity. In this study, we showed that celastrol combined with EGFR-TKIs significantly suppressed cell invasion of lung cancer cells with a T790M mutation by suppressing the EGFR pathway. Combined therapy with celastrol and EGFR-TKIs inhibited tumor growth in vivo . Together, these results suggested that combined therapy with EGFR-TKIs and celastrol may be a more effective treatment of patients with non-small-cell lung cancer with T790M mutations of the EGFR.